Digital Literacy and Science Literacy: A Correlational Review of Elementary School Students - Zainuri, Baiq Nabila Saufika; Gunawan , Gunawan; Qothrunnada, Qothrunnada (Indonesian Publication Center, 2025)
This study aims to analyze the correlation between digital literacy and science literacy in elementary school students through a systematic literature review covering the period 2015-2024. The method used is Systematic Literature Review (SLR). Literature search was conducted through Google Scholar, ERIC, Scopus, and Portal Garuda databases to identify relevant studies involving elementary school students. The results of the review consistently show a positive correlation between digital literacy skills and students' science literacy levels. The integration of innovative digital media, such as digital flipbooks, STEM-based comics, digital storytelling, and the use of QR Code technology, has been proven effective in helping students visualize abstract scientific concepts in a more concrete way, thereby improving their inquiry and problem-solving skills. This literature study concludes that digital literacy and science literacy are two mutually reinforcing competencies. The implications of this research emphasize the importance of a basic education curriculum that holistically integrates technological skills into science learning to shape a critical and adaptive generation.